Poetry and Moral Education in Teaching Learning Literature - Widyahening, Ch. Evy Tri (Sebelas Maret University, 2016)
Â In teaching learning literature, students are not only given by the materials which have the cognitive aspect but also they need to be given education which is related to the values of morale which can be utilized in their life. The values of morale heavily contained in literary works either that Indonesian literary works or literary works from English or American. Literary works which can be given to the students can be in the form of drama, prose or poetry. Poetry represnts one of literary works which can be used in giving morale education in teaching learning literature and can be integrated also in teaching learning language which is related to four language skills those are speaking, reading, writing and listening. In teaching learning process, a lecturer does not only give materials theoretically but also he or she gives assignments which are capable to train studentsâ creativity. A lecturer is also helped if he or she has a good textbook which can be used as a source in giving poetry materials theoretically and practically. Besides that, students are given an assignment to analyze the content of poems, they are also given an assignment to read the poems, and then they are asked to sing the poems with their own creativity with music which they make by themselves in a team-work. It will be very helpful for the students in comprehending teaching learning literature and it is able to sharpen their emotion, empathy, sympathy, and respect to others through poems.